КОМУ З БРАТІВ ЛАЗАРЕВСЬКИХ АДРЕСОВАНО ШЕВЧЕНКІВ ЛИСТ ВІД 20 ГРУДНЯ 1847 РОКУ? - Боронь, Олександр (Problems of Contemporary Literary Studies / Problemy Suchasnoho Literaturoznavstva, 2019)
The paper studies the publication history of Shevchenko’s letter of December 20, 1847, initially as one addressed to Vasyl Lazarevsky (first published in the journal «Kievskaja starina» in 1891), and then as one addressed to his brother Mykhailo. The decision was proposed in 1929 by M. Novitsky, the compiler of the complete works of Shevchenko (edited by S. Yefremov), on the basis of the content of M. Lazarevsky’s answer to Shevchenko on February 12, 1848. Subsequently, in all the academic collections of Shevchenko’s works, including the latest one in 12 volumes, this letter was identified as addressed to M. Lazarevsky. Already in 1993, a Russian researcher L. Bolshakov reasoned against such addressing, applying new and little-known material, in particular V. Lazarevsky’s memoirs, to the problem consideration. It turns out necessary to study L. Bolshakov’s arguments in order to accept or reject his version, on which further publishing decisions depend. Having analyzed Russian researcher’s evidence, the author refutes his hypothesis. The author bases on the previously ignored facts and additional arguments, in particular M. Lazarevsky’s statement in a letter of February 12, 1848 that he had not seen V. Dal, whereas V. Lazarevsky had met with him several times by that day. By the time of writing the analyzed letter, V. Lazarevsky had written Shevchenko only once (with brother Fedir), while poet’s friendship with M. Lazarevsky was substantially closer, because they knew each other personally and had met more than once. Obviously, in the first publication of 1891, O. Lazarevsky, being not aware enough of the details of his brothers’ relations with Shevchenko, was mistaken in identifying the addressee. The author of the paper concludes that L. Bolshakov’s hypothesis is not sufficiently grounded, while M. Novitsky’s decision, despite some minor inaccuracies, is entirely justified and appropriate. Next academic complete works should, therefore, include Shevchenko’s letter of December 20, 1847 as one addressed to M. Lazarevsky.